Attitudes towards prisoner-to-prisoner bullying and the association with prison environments: examining the components. Issue 2 (11th April 2016) - Ireland, Jane L.; Ireland, Carol A.; Power, Christina L
Abstract : Purpose: – The purpose of this paper is to examine attitudes towards prisoner-to-prisoner bullying, further considering the association between attitudes and characteristics of the prison environment thought to promote prisoner bullying. Design/methodology/approach: – Questionnaires were administered to 423 adult male prisoners and 195 correctional officers from three prisons in Canada. Participants completed the Prison Bullying Scale and the Prison Environmental Scale. Findings: – Convergence in attitudes between prisoners and officers were noted although staff were more likely to consider bullies to be skilled, whereas prisoners were more likely than officers to feel that victims of bullying should be supported. Associations between attitudes supportive of bullying and environmental characteristics likely to promote prison bullying were found primarily among prisoners; the strongest predictors of such attitudes were poor relationships (e.g. prisoner to officer; prisoner-to-prisoner). Research limitations/implications: – The study highlights the importance of the social aspect of the prison environment. It further provides an outline of two measures that could have utility in evaluating interventions designed to reduce prisoner-to-prisoner bullying. Practical implications: – Interventions into prisoner-to-prisoner bullying should attend to the wider environment and not focus solely on individual pathology approaches. A "whole prison" approach to intervention should be adopted, with recognition that officers and prisoners are part of the community. A focus on the perceived relationships between all those in this community requires consideration, with a community centred approach recommended for intervention. A concentrated effort is needed on evaluating and publishing interventions into prisoner-to-prisoner bullying. Originality/value: – The study is the first to examine attitudes in a combined sample of prisoners and officers and focuses on the role of the wider prison environment. It also utilises a sample from three prisons as opposed to focusing on a single establishment.